2012
DOI: 10.1071/hc12131
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand pharmacists’ experiences, practices and views regarding antibiotic use without prescription

Abstract: INTRODUCTION: Very few studies have investigated pharmacists’ views, experiences and practices regarding the use of antibiotics without prescription. This study aimed to explore through self-report and hypothetical scenarios what factors determine New Zealand pharmacists’ behaviour and attitudes towards non-prescription use of antibiotics. METHODS: A purposeful sample of 35 registered community pharmacists of differing ethnic backgrounds was selected from a mixture of pharmacies that predominantly either serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Some of the dispensing malpractices seen in developing countries are attributed to the low level of adherence to the existing laws and regulations on good dispensing practice, lack of knowledge and professionalism among pharmacists, demand from consumers, and business orientation of pharmacies [19]. Nigeria is not left out as this study revealed that 85% of the community pharmacists surveyed dispensed prescription only medications without valid prescriptions as opposed to demanding for the prescription order as required law before dispensing such medications.…”
Section: Discussionmentioning
confidence: 87%
“…Some of the dispensing malpractices seen in developing countries are attributed to the low level of adherence to the existing laws and regulations on good dispensing practice, lack of knowledge and professionalism among pharmacists, demand from consumers, and business orientation of pharmacies [19]. Nigeria is not left out as this study revealed that 85% of the community pharmacists surveyed dispensed prescription only medications without valid prescriptions as opposed to demanding for the prescription order as required law before dispensing such medications.…”
Section: Discussionmentioning
confidence: 87%
“…Two studies in Saudi Arabia [40] and China [41] demonstrated the practice of dispensing antibiotics without prescriptions by most CPs that is associated with the overuse of antibiotics and the risk of developing AMR. Such practices have been aggravated by financial incentives [42,43]. The economic interventions that may change CPs' attitudes to avoid dispensing antibiotics without a prescription could be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial proportion of the total drug budget in many developing countries, including Ethiopia, is dedicated to antimicrobials and they are often the largest group of drugs purchased [22]. Even though the extent of nonprescription sale of antibiotics is not extensively studied in Ethiopia, the financial incentives and business orientation of pharmacies, which are known to be reasons for dispensing malpractice [23], need to be fully resolved for planning intervention strategies to curb antimicrobial resistance. The present study showed that about 42.1% of community pharmacists often/always took part in antimicrobial awareness movements.…”
Section: Discussionmentioning
confidence: 99%